Anticancer Activity of Turmeric Rhizome Extract (Curcuma longa Linn) In-vitro Against MCF7 Breast Cancer Line Cells - Halimatushadyah, Ernie; Rahayu, Ani (Poltekkes Kemenkes Kendari, 2023)
Turmeric or Curcuma longa Linn is one of the native spices and medicinal plants from Southeast Asia. Turmeric contains a compound named curcumin. Curcumin (diferuloylmethane) is a yellow pigment in turmeric that is widely used as a spice, food coloring (curry) and preservative. Curcumin shows various pharmacological effects that have been reported scientifically in research, one of which is as an anticancer. This study aims to perform a cytotoxic test of turmeric rhizome extract (Curcuma longa Linn) in-vitro with the Microtetrazolim (MTT) assay method to grasp and determine the effect of preventing the growth of MCF7 breast cancer cells, so that the IC50 value can be known. In this study, it was found that turmeric rhizome extract can be used as a natural ingredient that has the potential to inhibit the growth of MCF7 breast cancer cells. Turmeric rhizome extract has the effectiveness to inhibit the growth of MCF7 breast cancer cells with an IC50 value of 26.30 ppm. This value is categorized as moderate or moderately active cytotoxic.